Comparison of autonomic activity between pre and post menstrual period - Kale, Jyoti Sahebrao; Katole, Nilesh Tulsiram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Autonomic nervous system play important role in premenstrual stress. In present study we compare autonomic functions between premenstrual and postmenstrual phases in young females. Methods: The study was carried out on 50 eumenorrheic healthy female of 17 to 25 years of age observed on pre and post menstruation. Autonomic parameters like basal pulse rate, basal blood pressure and cold stimulus test was carried out in pre and post menstrual phases. Data was analyzed by using paired t-test. Results: There was significant increase (P <0.001) in pulse rate, blood pressure, systolic and diastolic response to cold stimulus during premenstrual period as compared to postmenstrual period. Conclusions: There was significant increase (P <0.001) in pulse rate, blood pressure, systolic and diastolic response to cold stimulus during premenstrual period as compared to postmenstrual period.